Induction of Interleukin-8 from Nasal Epithelial Cells during Bacterial Infection: The Role of IL-8 for Neutrophil Recruitment in Chronic Rhinosinusitis - Bit-Na Yoon; Nan-Geum Choi; Hyun-Sun Lee; Kyu-Sup Cho; Hwan-Jung Roh (Hindawi Limited, 2010)
Objectives. The aim of this study was to elucidate the role of IL-8 for neutrophil recruitment in nonallergic CRS patients. Methods. After coculture of Streptococcus pneumoniae (SP) with the mucosal epithelial cells (MECs) from non-CRS patients, at three different SP/MEC (1/1, 10/1, 100/1) ratios, the expression of IL-8 mRNA and the concentration of IL-8 were measured by RT-PCR and ELISA. The expression of CD11b/CD18 on neutrophils and E-selectin/ICAM-1 on endothelial cells and the adherence between neutrophils and human umbilical vascular endothelial cells (HUVECs) were determined by flow cytometric analysis, ELISA, and RIA, respectively. Results. IL-8 concentration and IL-8 mRNA expression continued to increase from 3 hours after incubation in SP number-dependent manner. The expression of CD11b/CD18 on neutrophils and E-selectin/ICAM-1 on HUVECs, and the adherence between neutrophils and HUVECs were significantly increased in 10 SP/MEC-CM, and the increments were significantly blocked by anti-IL-8 antibody. Conclusion. MEC and IL-8 are major factors for neutrophil recruitment in nonallergic CRS.